2004
DOI: 10.1051/parasite/2004111103
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma vivax: a simplified protocol forin vivogrowth, isolation and cryopreservation

Abstract: S u m m a ry :A rodent ad apte d clone o f Trypanosoma vivax w as used to infect cyclophospham ide treated mice and rats. Fresh blood containing trypanosomes, w as centrifuged in a density gradient of three Percoll solutions, 1 .0 7 , 1 .0 6 , 1 .0 5 g /m l, respectively, carefully layered on top o f each other. The yields o f this simple procedure for trypanosome purification w ere about six times higher than those obtained w ith the conventional anion-exchange columns. C ryopreservation o f trypanosomes usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 1 publication
0
9
0
1
Order By: Relevance
“…IL 1392 was chosen for its stable expression of VSG ILDat 1.2, characteristic of rodent-adapted West African T. vivax isolates that together with closely related South American stocks pertain phylogenetically to the same clade [66]. Initially, our studies showed that the IL 1392 isolate, retained its infective characteristics and mouse infection profile after a long cryopreservation period (see Material and Methods) [11], [22]. In addition, the experimental mouse models used in this work proved easy to handle on infection and reflected the general characteristic features observed in livestock, namely the remodeling of secondary lymphoid organs, cardinal severe anemia, genetically-related differences in resistance to the parasite (but not to death) and the development of multifocal tissue hemorrhages, necrosis and consequent systemic pathologies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…IL 1392 was chosen for its stable expression of VSG ILDat 1.2, characteristic of rodent-adapted West African T. vivax isolates that together with closely related South American stocks pertain phylogenetically to the same clade [66]. Initially, our studies showed that the IL 1392 isolate, retained its infective characteristics and mouse infection profile after a long cryopreservation period (see Material and Methods) [11], [22]. In addition, the experimental mouse models used in this work proved easy to handle on infection and reflected the general characteristic features observed in livestock, namely the remodeling of secondary lymphoid organs, cardinal severe anemia, genetically-related differences in resistance to the parasite (but not to death) and the development of multifocal tissue hemorrhages, necrosis and consequent systemic pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…T. vivax - specific forward and reverse ribosomal promoter primers were also deduced from the Zaria Y486 chromosome 3: TvrDNAF (5' CTGATTTCGCCACTGCTATTATTTGC 3') and TvrDNAR (5' CGCTTCACTTGATGATCGTTTCG 3'), respectively. Parasites were maintained by weekly passages in mice and new stabilates were appropriately and regularly frozen in polysoma buffer/glycerol, as previously described [11]. Blood smears were prepared from infected mouse blood, air dried, fixed in methanol for 5 minutes and further stained with 5% Giemsa for 20 minutes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is thus necessary to produce the antigens by cultivation in sheep or cattle, host species in which separation of parasites and blood cells on DEAE-cellulose is quite difficult and produces inconsistent results. For this reason, some authors proposed a technique based on the use of a Percoll gradient (Ndao et al 2004) or even the combined used of a gradient and DEAE-cellulose (Gonzalez et al 2005). However, a rodent adapted strain of T. vivax from French Guiana is now available at the Centre International de Recherche Développement de l'Elevage en Zone subhumide, Bobo Dioulasso, Burkina Faso (M Desquesnes unpublished observations).…”
Section: Isolation and Purification Of Blood Trypanosomesmentioning
confidence: 99%